Peran Moderasi Lever of Control (LoC) dalam Pengaruh Budaya, Strategi, dan Ketidakpastian Lingkungan terhadap Kinerja Perusahaan - Lativa Lativa; Regina Jansen Arsjah (Society, 2024)
This study examines the impact of corporate culture, strategic orientation, and environmental uncertainty on firm performance, focusing on the moderating role of the Lever of Controls (LoC). Primary data were collected through a survey involving 203 respondents from both listed and unlisted companies in Indonesia on the Indonesia Stock Exchange. Firm performance was measured using customer satisfaction, revenue, profit growth, return on investment, and market share. The findings reveal that corporate culture and strategic orientation significantly enhance firm performance. However, environmental uncertainty was found to have no direct impact on business performance. Furthermore, the moderating role of the LoC was not validated, suggesting that the relationship between management control systems and performance is complex and requires further investigation, particularly in uncertain environments. This research provides valuable insights for practitioners, emphasizing that firm performance is strongly influenced by corporate culture, strategic orientation, and effective management of environmental uncertainty.